PENGARUH PEMBERIAN BERBAGAI JENIS BOKASHI TERHADAP PERTUMBUHAN DAN HASIL BAWANG MERAH PADA TANAH ALLUVIAL - man, razibullah (Jurnal Sains Pertanian Equator, 2019)
This study aims to determine the type of bokashi that is best for the growth and yield of shallots on alluvial soil. This research was carried out on the Tanjungpura University Faculty of Agriculture experimental field in Pontianak which took place January 26th 2018 to March 27th 2018. The method used was Randomized Block Design (RBD) consist of 4 treatments, 6 replications, and 16 sample plants. Giving various types of bokashi including p1 = 20 tons / ha of Mesona spp waste bokashi; p2 = 20 tons / ha of vegetable waste bokashi, p3 = 20 tons / ha of Eichhornia crassipes bokashi and p4 = 20 tons / ha Hymenachine amplexicaulis bokashi. Variabeles observed were plant height, number of tillers, dry weight of plants, number of tubers per clump, fresh weight of tubers per clump, fresh weight of tuber per plot, dry weight of tuber clump and dry weight of tuber per plot. The results of the study concluded that the best types of bokashi for growth and yield of shallots on alluvial soil have not been found, giving Mesona spp waste bokashi, vegetable waste bokashi, Eichhornia crassipes bokashi and Hymenachine amplexicaulis bokashi providing the same growth and yield of shallots on alluvial soil. Keywords: alluvial, bokashi, shallots